2022
DOI: 10.3389/fimmu.2022.871661
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor (CAR)-T Cell Immunotherapy Against Thoracic Malignancies: Challenges and Opportunities

Abstract: Different from surgery, chemical therapy, radio-therapy and target therapy, Chimeric antigen receptor-modified T (CAR-T) cells, a novel adoptive immunotherapy strategy, have been used successfully against both hematological tumors and solid tumors. Although several problems have reduced engineered CAR-T cell therapeutic outcomes in clinical trials for the treatment of thoracic malignancies, including the lack of specific antigens, an immunosuppressive tumor microenvironment, a low level of CAR-T cell infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 197 publications
0
4
0
Order By: Relevance
“…In this line, image-guided insertion of these T cells is being tested in patients with pleural malignancies [91] or in combination with the anti-PD-1 agent pembrolizumab [92]. Even though, in this type of tumor, the search of an adequate, specific TAA that directs the immune reaction towards the tumor cells and causes minimal damage to healthy cells is very complex, unlike what occurs in hematological neoplasms with CD19, and the solution of this problem will be in the numerous clinical trials with such different approaches [93].…”
Section: Immunotherapy With Genetically Modified T Cellsmentioning
confidence: 99%
“…In this line, image-guided insertion of these T cells is being tested in patients with pleural malignancies [91] or in combination with the anti-PD-1 agent pembrolizumab [92]. Even though, in this type of tumor, the search of an adequate, specific TAA that directs the immune reaction towards the tumor cells and causes minimal damage to healthy cells is very complex, unlike what occurs in hematological neoplasms with CD19, and the solution of this problem will be in the numerous clinical trials with such different approaches [93].…”
Section: Immunotherapy With Genetically Modified T Cellsmentioning
confidence: 99%
“…At present, the field of immunotherapy is mainly focused on chimeric antigen receptor T cell immunotherapy (CAR-T) and checkpoint inhibitors (ICI), both of which aim to target cytotoxic T cells for the elimination of tumor cells. However, several problems reduce the therapeutic effect, including an immunosuppressive tumor microenvironment, a low level of drug infiltration into tumor tissues, off-target toxicity and other safety issues [143][144][145]. Furthermore, studies have shown that in order to achieve more powerful anti-tumor immune responses combined with immunotherapy, which can stimulate several different types of immune cells, needs to be considered [146,147].…”
Section: Immunotherapymentioning
confidence: 99%
“…The canonical “second generation” CAR recognizes target antigen by an extracellular single chain fragment of variable region (scFv) antibody that is composed of the variable domains of the antibody heavy (VH) and light (VL) chains tethered together by a short flexible linker in the order VH-VL or VL-VH ( 16 , 17 ). A hinge region physically connects the scFv to the transmembrane domain and is usually derived from the IgG1 CH2-CH3 region, the extracellular part of CD28 or from the hinge domain of the CD8α molecule ( 18 ). Generally, the intracellular signaling part of a CAR comprises the CD3ζ chain to provide the primary signal and a costimulatory domain to augment and prolong activation, frequently derived of the intracellular part of CD28 or 4-1BB ( 18 ).…”
Section: Modifying the Carmentioning
confidence: 99%
“…A hinge region physically connects the scFv to the transmembrane domain and is usually derived from the IgG1 CH2-CH3 region, the extracellular part of CD28 or from the hinge domain of the CD8α molecule ( 18 ). Generally, the intracellular signaling part of a CAR comprises the CD3ζ chain to provide the primary signal and a costimulatory domain to augment and prolong activation, frequently derived of the intracellular part of CD28 or 4-1BB ( 18 ). To enhance the antigen sensitivity, each CAR component can accordingly modified ( Figure 1 ).…”
Section: Modifying the Carmentioning
confidence: 99%